HLA B(∗)5701 status, disease progression, and response to antiretroviral therapy (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: In addition to hypersensitivity reactions to abacavir, HLA B(∗)5701 has been associated with slow or nonprogression of HIV infection. We explored the effect of HLA B(∗)5701 on CD4(+) cell count and viral load in untreated patients and on responses to nonabacavir-containing combination antiretroviral therapy (cART) in a large UK-based cohort. DESIGN: Analysis of a cohort of HIV-infected adults. METHODS: In untreated patients, CD4(+) cell count and viral load at study entry were compared in HLAB(∗)5701-positive and HLAB(∗)5701-negative individuals and linear regression tested for an interaction effect of viral load and HLA B(∗)5701 on CD4(+) cell count. In patients starting a nonabacavir cART regimen, Cox proportional hazards models compared virological responses to cART among HLA B(∗)5701-negative, HLA B(∗)5701-positive, and those not tested. Six-month and 12-month changes in CD4(+) cell count were used as outcomes in linear regression to compare immunological response to cART in these groups. RESULTS: ART-naive HLA B(∗)5701-positive individuals had higher CD4(+) cell count (P <0.0001) and lower viral load (P <0.0001) at study entry than negatives; however, HLA B(∗)5701 status was not found to effect the association between viral load and CD4(+) cell count (interaction P value = 0.09). HLA B(∗)5701-positive patients were more likely to achieve viral suppression than negative patients on a nonabacavir regimen [hazard ratio = 1.29, 95% confidence interval, CI (1.15–1.54)] and less likely to experience viral rebound [hazard ratio = 0.61, 95% CI (0.37–0.99)]. CONCLUSION: Better virological but not immunological responses to cART were seen in HLA B(∗)5701-positive patients on nonabacavir regimens. This study provides further evidence of the potentially beneficial effect of HLA B(∗)5701 on HIV progression.